Safety and Efficacy of Bone Marrow and Adipose Tissue Mesenchymal Stem Cells in the Treatment of Spinal Cord Injury: A Preliminary Study: BM-MSCs vs AT-MSCs in SCI treatment - Jamali, Fatima; Alqudah, Mahmoud; Dahbour, Said; Alhattab, Dana; Bawa'neh, Hisham; Rahmeh, Reem; Samara, Osama; Awidi, Abdalla (Jordan Medical Journal, 2024)
Background: Mesenchymal stem cells (MSC) of various origins are the most widely investigated type of stem cells in clinical trials. We report a treatment comparison of two adult sources of autologous MSCs regarding safety and efficacy in established spinal cord injury (SCI). Materials and Methods: In this Phase I/II open-label two-arm study, patients were divided into two groups. The first group was treated with autologous bone marrow-derived MSCs (BM-MSC), while the second was treated with autologous adipose tissue-derived MSCs (AT-MSC). Safety and outcomes were assessed in both groups for 24 months post-treatment initiation using the American Spinal Injury Association (ASIA) Impairment Scale (AIS). Results: Both groups showed no serious treatment-emergent adverse events (TEAEs). AIS-assessed outcomes pointed to sensory and motor improvements in patients of both groups. Patients who received AT-MSCs showed better sensory and motor function improvement than those who received BM-MSCs. One patient in the AT-MSCs group regained the ability to walk after years of disability. Conclusions: Intrathecal injection of autologous AT-MSCs and autologous BM-MSC appears to be safe, with a possible advantage in the AT-MSCs treatment option regarding efficacy over BM-MSCs. Future clinical trials investigating larger sample sizes are warranted for wider use of this treatment modality in clinical practice. Furthermore, earlier use of cellular therapy intervention for SCI patients is predicted to improve the benefits. Trial registration: clinicaltrials.gov identifier: NCT02981576